EFISIENSI PENGGUNAAN PROTEIN OLEH BABI YANG MENDAPAT PAKAN MENGANDUNG TEPUNG TEMULAWAK (Curcuma xanthorrhiza) (Protein efficiency of pigs fed with diets containing temulawak (Curcuma xanthorrhiza meals) - Ninengah suryani; I Made Suaba Aryanta (JURNAL NUKLEUS PETERNAKAN, 2020)
The aimed of this study was to determine the effect of Curcuma xanthorrhiza meal 0%, 0.5%, 0.75% and 1% on the efficiency of protein use (protein consumption, protein intake, body weight gain and protein efficiency ratio (REP). Twelve castration male pigs aged 3 months with an average body weight of 33.8 kg (CV = 23%). This study used a randomized block design (RBD) with four treatments and three replications. The treatment diets namely: R0 (100% basal diet without curcumin meal), R1 (basal diet + 0.5% curcumin meal), R2 (basal diet + 0.75% curcumin meal and R3 (basal deat + 1% curcumin meal). The results showed that the addition up to 1% had no significant effect on ration consumption, protein consumption, protein utilization and PER (P <0.05). It was concluded that the addition up to 1% curcuma meal could not increased protein efficiency on growing pigs.